2018
DOI: 10.1103/physrevb.97.085148
|View full text |Cite
|
Sign up to set email alerts
|

Topological transitions in continuously deformed photonic crystals

Abstract: ¶ These authors contributed equally. Abstract:We demonstrate that multiple topological transitions can occur, with high-sensitivity, by continuous change of the geometry of a simple 2D dielectric-frame photonic crystal consisting of circular air-holes. By changing the radii of the holes and/or the distance between them, multiple transitions between normal and topological photonic band gaps (PBGs) can appear. The time-reversal symmetric topological PBGs resemble the quantum spin-Hall insulator of electrons and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…In photonics, such phenomena can emerge in systems with [32][33][34][35][36][37][38] or without [39] time-reversal symmetry. In the literature, there are various proposals for photonic topological insulators [32][33][34][35][36][37][38][39][40][41]. For simplicity, we shall consider 2D all-dielectric photonic crystals for the transverse-magnetic modes, which can be realized by metallic plates cladding along the z direction [38].…”
Section: Quantum Spin Hall Effect and Fragile Topology In Photonic Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In photonics, such phenomena can emerge in systems with [32][33][34][35][36][37][38] or without [39] time-reversal symmetry. In the literature, there are various proposals for photonic topological insulators [32][33][34][35][36][37][38][39][40][41]. For simplicity, we shall consider 2D all-dielectric photonic crystals for the transverse-magnetic modes, which can be realized by metallic plates cladding along the z direction [38].…”
Section: Quantum Spin Hall Effect and Fragile Topology In Photonic Anmentioning
confidence: 99%
“…Helical edge states, the hallmark of quantum spin Hall effects, have been widely studied in photonic and acoustic system [32][33][34][35][36][37][38][59][60][61]. Here we perform calculations for the edge states using the sonic crystals studied in section 3.3.…”
Section: Quantum Spin Hall Effect and Helical Edge Statementioning
confidence: 99%
“…In the last few years, it could be shown that the non-reciprocal behaviour of magneto-optical materials like InSb has very interesting consequences for nanoscale thermal radiation. For example, fundamental effects like a persistent heat-current [1,2], giant magnetoresistance [3,4], thermal Hall effect [5] as well as a circular heat flux, angular momentum, and spin which do also persist in global equilibrium [6] were highlighted. As reviewed and discussed in detail in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Usually topological edge states appear when one of the materials forming the interface is periodic and possesses specific degeneracies in its spectrum. Edge states at the interfaces of such mate-rials (including those with honeycomb and hexagonal structure) may be created by introducing deformations into underlying lattices [13], by varying spacing between lattice sites across the interface, introducing detuning between sublattices, changing orientation of anisotropic elements placed in the lattice nodes, and realization of anisotropic coupling between different lattice sites. They have been suggested and observed in electromagnetic systems, including photonic crystals [14][15][16], periodic metamaterial structures [17,18], shallow waveguide arrays [19], for acoustic [20] and elastic [21] waves, polaritons [22], as well as for electronic states in two-dimensional materials [23].…”
Section: Introductionmentioning
confidence: 99%